The Review on the Antimicrobial Potential of Maidenhair Fern, Adiantum capillus-veneris L. (Annals of the Institute of Biology, 2023)
Adiantum capillus-veneris L. or Maidenhair fern is a perennial fern that belongs to the family Pteridaceae. It is widespread in temperate and tropical regions with high humidity. A. capillus-veneris has a long history of medicinal use, and recent investigations suggest the presence of many bioactive compounds in this plant. This review debates the antimicrobial potential of Adiantum capillus-veneris in a comprehensive manner that includes data about the antibacterial, antifungal, and antiviral activity. Data regarding the antimicrobial potential of A. capillus-veneris were collected from scientific databases Web of Science, Scopus, PubMed, and Google Scholar. The largest number of reviewed studies were related to the antibacterial activity of extracts made from A. capillus-veneris plant. Mainly, leaves, stems, roots, and rhizomes were tested, while water, methanol, ethanol, ethyl acetate, and hexane were used as solvents. For the testing of antimicrobial susceptibility, standard tests were implemented, such as the disk-diffusion method, agar dilution method, and determination of MIC and MBC values. There are also studies testing the antibiofilm effects of the investigated plant. Our review showed that A. capillus-veneris exhibits large antibacterial potential, with the capacity to inhibit the growth of different bacteria, including multidrug-resistant strains. The antifungal and antiviral activity of the investigated plant was also recorded. This review summarized data regarding the antimicrobial potential of A. capillus-veneris and suggests that future phytochemical investigations of ferns may lead to the discovery of new therapeutic agents.